Why Has Inflation Been So Low since 1999? - Nickell, S (2005)
In this paper,(1) Stephen Nickell, member of the Bank's Monetary Policy Committee (MPC), explains why CPI goods prices have been falling in the United Kingdom since mid-1999. From 1999 to early 2001, the main factor was a squeeze on margins in the distribution sector. Since then, falling import prices have played a key role along with strong distribution sector productivity growth. Looking forward, while the latter should continue to play a role, import prices may well start to rise. This is consistent with CPI inflation moving up to the 2% target over the next two years.